Management of outflow tract ventricular arrhythmias. (January 2015) - Maury, Philippe; Rollin, Anne; Mondoly, Pierre; Duparc, Alexandre
<x xml:space="preserve">Abstract</x> Purpose of review Outflow tract ventricular arrhythmias represent an important chapter in clinical electrophysiology. Recent investigations enhance the knowledge in that field and highlight new important concepts in ventricular arrhythmogenesis. Recent findings Recent publications have revealed new interesting results in the field of outflow tract ventricular arrhythmias. The embryonic phenotype is maintained in the adult outflow tract, which leads to conduction slowing in some circumstances. Outflow tract ventricular arrhythmias unrelated to any detectable abnormal area may happen in structural heart disease. Promising results are expected using noninvasive high-density ECG mapping for outflow tract ventricular arrhythmia localization. In an experimental model of Brugada syndrome, late fractionated activity at the outflow tract was shown to result from repolarization heterogeneity. Malignant ventricular arrhythmias from the right ventricular outflow tract should be suspected in case of syncopal episode and when ectopies display a positive QRS complex in lead I. Ablation was shown to be superior to drug therapy for outflow tract ventricular arrhythmia in a recent prospective randomized study. Recent reports described novel previously unsuspected locations for ventricular arrhythmia, while some still poorly recognized structures are implicated in outflow tract ventricular arrhythmia. Summary Recent findings have shed new light on the basic and clinical electrophysiology of the outflow tract, which may enhance the management of patients with benign outflow tract ventricular arrhythmia and solve the complex relationships between outflow tract ventricular arrhythmia and sudden death.